The Contradictory Legacy of Zionism: Radical Religious Groups - Leyla Kuşaslan (Milel ve Nihal)

(untitled)
Zionism initially emerged as a secular movement aimed at the national liberation of the Jewish people. Most Zionist leaders, known as the founding fathers, sought to dissociate Judaism from its religious identity and embed it within a modern nationalist framework. The desire to establish a national consciousness while sidelining religious teachings led to significant conflicts and schisms among both secular and religious Jewish communities. Aside from a small minority within religious groups, Zionism was largely rejected and scorned by religious Jews in its early days. However, the establishment of the state, particularly following the Six-Day War in 1967, paradoxically provided fertile ground for the rise of religious radicalism. Religious groups began interpreting the acquisition of sacred lands, such as Jerusalem and the West Bank, as a divine sign, advocating for Israel’s expansion as a religious mission. This study will examine the contradictory legacy of Zionism, characterized by its secular, and at times anti-religious, ideology. Zionism continues to create deep divisions within Israeli society, perpetuating a persistent tension between secular and religious identities. Radical Zionist religious groups legitimize violence against Palestinians, sustaining a profound area of conflict in Israeli politics and settlement policies.